2019
DOI: 10.1101/2019.12.21.886093
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Longitudinal linked read sequencing reveals ecological and evolutionary responses of a human gut microbiome during antibiotic treatment

Abstract: Gut microbial communities can respond to antibiotic perturbations by rapidly altering their taxonomic and functional composition. However, little is known about the strain-level processes that drive this collective response. Here we characterize the gut microbiome of a single individual at high temporal and genetic resolution through a period of health, disease, antibiotic treatment, and recovery. We used deep, linked-read metagenomic sequencing to track the longitudinal dynamics of thousands of single nucleot… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(42 citation statements)
references
References 70 publications
(120 reference statements)
3
39
0
Order By: Relevance
“…However, connecting these processes may not always be straightforward. 39 Similar to our finding, in a recent analysis of longitudinal linked-read sequencing data from human gut microbiota subjected to antibiotic treatment, antibiotic resistance mutations were found to sweep to high frequencies in the populations of single species without necessarily resulting in an increased abundance of the species in the community 18 . In a microbial community, species sorting and adaptive mutations occur simultaneously in multiple species, and all these factors have the potential to interact, making it challenging to disentangle ecological from evolutionary processes.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…However, connecting these processes may not always be straightforward. 39 Similar to our finding, in a recent analysis of longitudinal linked-read sequencing data from human gut microbiota subjected to antibiotic treatment, antibiotic resistance mutations were found to sweep to high frequencies in the populations of single species without necessarily resulting in an increased abundance of the species in the community 18 . In a microbial community, species sorting and adaptive mutations occur simultaneously in multiple species, and all these factors have the potential to interact, making it challenging to disentangle ecological from evolutionary processes.…”
Section: Discussionsupporting
confidence: 89%
“…Intriguingly, in the case of antibiotics, while there is an extensive number of studies on both the species compositional effects of antibiotic perturbation on the microbiome and the genetics of antibiotic resistance in individual species, both aspects have rarely been analyzed together. Furthermore, high-throughput sequencing based approaches allowing the investigation of mutations in longitudinal microbiome data have focused on in vivo and field samples where the species are uncultured and the pre-existing traits of the species cannot be explicitly estimated 18 . This confounds the ability to assess the importance of evolution relative to species sorting.…”
Section: Introductionmentioning
confidence: 99%
“…They found that antibiotic-naive children harbored increased strain-level diversity of Bacteroides fragilis, a key commensal important for immune education and bacterial tolerance [28,89]. Harboring more strains of the same species is believed to be a component of a resilient microbiome as well as providing different functions [37,90,91]. It is likely possible to achieve microbiome health and resilience to perturbation either by increased strain-level diversity within a species or by maintenance of a diverse array of different species.…”
Section: Vulnerable Infancy and Dynamic Childhoodmentioning
confidence: 99%
“…Experimentalists are examining evolutionary rescue in a community context. The examples include microbiomes adapting to antibiotic treatment (Roodgar et al, 2019); soil microbial communities adapting to herbicides (Low-Décarie et al, 2015) and lacustrine plankton communities adapting to acidification (Bell et al, 2019). There are many more situations in which CWR could be considered as a potential mechanism for rare species loss, as many ecosystems face irreversible human induced environmental change on a community-wide level (Vitousek et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Whilst many models exist that study how a population of a single species, or a community composed of two species, adapts to environmental change (Hoffmann and Sgrò, 2011;Martin et al, 2013;Northfield and Ives, 2013;Osmond and De Mazancourt, 2013;Cortez and Yamamichi, 2019), fewer models exist that describe the response of an entire community composed of multiple species to an altered environment, although there are some examples (De Mazancourt et al, 2008;Bell, 2017;Lasky, 2019). Furthermore, empirical results, describing community wide adaptation, such as those presented by Bell and Gonzalez (2011), Low-Décarie et al (2015), Bell et al (2019), and Roodgar et al (2019), are clearly calling for such models.…”
Section: Introductionmentioning
confidence: 99%